Acute methotrexate toxicity: experience in a tertiary care hospital of Bangladesh - Islam, Mohammad Tajul; Haque, Hasna Fahmima; Islam, Md Jubaidul; Chakraborty, Ranodhir; Rahman, Shahin Ibn; Ahmed, AKM Shaheen (BIRDEM Medical Journal, 2025)
Background: Methotrexate (MTX) is one of the commonly prescribed disease-modifying anti-rheumatic drugs (DMARDs) used in various rheumatic diseases. It can potentially cause life-threatening neutropenic sepsis and acute renal and hepatotoxicity when taken erroneously at high doses. Here, we present the clinical profile and risk factors of patients who presented with clinical features of acute MTX toxicity. Methods: This hospital based observational study was carried out in the Department of Internal Medicine, Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital, Dhaka, Bangladesh from July 2022 to May 2024. The clinical profile, risk factors and outcome of patients taking MTX erroneously at high doses were analyzed. Results: Total 12 cases including 8 females were taking erroneously higher dose of MTX. The mean age was 55 (range 40 - 67) years. Mean dose of MTX was 70 (range 60 - 200) mg on the week of toxicity. The reason for overdose in our cohort was daily intake instead of weekly. The major adverse event was thrombocytopenia and stomatitis (91.7%) with 58.3% having oral bleeding. Gastrointestinal adverse events like vomiting and diarrhoea were seen in 41.7% and 25% of the patients respectively. Our cohort had two patients who succumbed to the complications due to neutropenic sepsis. The dose of MTX did not correlate with the severity of the disease or duration of hospital stay; however, the latter was significantly influenced by lower absolute neutrophil count (ANC) 250 109/L. Conclusion: In our study two patient died, five patient needed ICU care and two patient developed severe neutropenic sepsis. So, sensitization of physicians is of paramount importance to clinch the signs of MTX toxicity at the earliest to avoid morbidity and mortality. BIRDEM Med J 2025; 15(2): 73-79